Suppression of miR-130a-3p Attenuates Oxygen–Glucose Deprivation/Reoxygenation-Induced Dendritic Spine Loss by Promoting APP - Zhu, Liang; Zhu, Lei; Tan, Jinyun; Chen, Kui; Yu, Bo (Frontiers in Neuroscience, 2021)
Background: Cerebral stroke induces neuronal dysfunction as a consequence of neuronal morphology changes. Emerging evidence suggests that microRNAs (miRNAs) may play an important role in regulating dysfunction in stroke, yet there are still few studies examining the association between whole blood miRNAs and neuronal morphology. The present study aimed to ascertain the potential roles and mechanisms of action of miR-130a-3p in ischemic stroke. Methods: The miRNA datasets of peripheral serum in the GEO database and the mRNA datasets of the human brain after ischemia were analyzed to identify differentially expressed RNAs, and their functions were verified in cultured neurons in vitro. Furthermore, the target gene was validated by dual-luciferase reporter assay, RT-PCR, Western blot, and immunofluorescence experiments. The identified miRNA was further verified by the OGD test to restore neuronal changes after ischemia through APP. Results: The expression of whole blood miR-130a-3p was found significantly lower in participants with ischemic stroke than in controls by analyzing expression profiling datasets of cerebral ischemia stroke obtained from the Gene Expression Omnibus (GEO) DataSets portal, which was confirmed in the MCAO model in mice. Furthermore, GO analysis showed that miR-130a-3p might directly affect neuronal function. Indeed, we demonstrated that miR-130a-3p played a central role in the inhibition of dendritic morphogenesis and in the growth of dendritic spines in vitro. We also confirmed that miR-130a-3p could regulate the expression of APP by luciferase reporter assay, RT-PCR, Western blot, and immunofluorescence experiments, which were consistent with the bioinformatic analysis. Last but not least, we also demonstrated that reducing miR-130a-3p expression partially rescued neuronal morphological changes after OGD in vitro. Conclusion: miR-130a-3p is a potential biomarker of cerebral stroke, can affect neuronal morphology through APP, and promote the repair of neurons by promoting APP expression after cerebral ischemia.